2014
DOI: 10.1016/j.cub.2014.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Axons Degenerate in the Absence of Mitochondria in C. elegans

Abstract: SUMMARY Many neurodegenerative disorders are associated with mitochondrial defects [1–3]. Mitochondria can play an active role in degeneration by releasing reactive oxygen species and apoptotic factors [4–7]. Alternatively, mitochondria can protect axons from stress and insults, for example by buffering calcium [8]. Recent studies manipulating mitochondria lend support to both of these models [9–13]. Here, we identify a C. elegans mutant, ric-7, in which mitochondria are unable to exit the neuron cell bodies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
100
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 27 publications
(29 reference statements)
14
100
1
Order By: Relevance
“…A recent study has shown that the presence of mitochondria in C. elegans axons protects from degeneration following axotomy (Rawson et al, 2014). To ascertain whether mitochondria might similarly modulate the rate of degeneration in PLM, we performed axotomies in animals carrying a mutation in the ric-7 gene that disrupts mitochondrial transport, resulting in the accumulation of mitochondria in neuronal cell bodies and a near complete absence in neurites (Rawson et al, 2014) (Figures 5A and S5).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has shown that the presence of mitochondria in C. elegans axons protects from degeneration following axotomy (Rawson et al, 2014). To ascertain whether mitochondria might similarly modulate the rate of degeneration in PLM, we performed axotomies in animals carrying a mutation in the ric-7 gene that disrupts mitochondrial transport, resulting in the accumulation of mitochondria in neuronal cell bodies and a near complete absence in neurites (Rawson et al, 2014) (Figures 5A and S5).…”
Section: Resultsmentioning
confidence: 99%
“…By examining a transgene marker expressing mitochondrial cytochrome C oxidase subunit-8 (Cox-8) Crimson fusion protein, we found that mitochondria are either at synaptic regions or very close to synapses in RMED/V neurites and DD motor neurons (Figure 2 A and S3 A), raising the possibility that mitochondria may also regulate synapse elimination in C. elegans . To test this hypothesis, we investigated the development of RME neurons in loss-of-function ric-7 (resistance to inhibitors of cholinesterase), which is essential for axonal localization of mitochondria in C. elegans (Rawson et al, 2014). We observed that loss-of-function in ric-7 blocked the distribution of mitochondria in D/V neurites, and displayed elimination phenotypes to a similar degree as CED mutants (Figure 3 A, B, C and D).…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, loss-of-function in ric-7 completely blocked axonal/synaptic localization of CED-3 and CED-9 (Figure S3 D and E), indicating that the axonal/synaptic localization of CED-9 and CED-3 depends on the presence of mitochondria in axons. Previous studies showed that transport of mitochondria in axons is mediated by a motor protein unc-116 in motor neurons (Rawson et al, 2014). However, we did not observe any strong defects in mitochondrion distribution in RME neurons of unc-116(lf) animals, and overexpression the mitochondrion targeted kinesin (Kinesin-TOM7) did not rescue mitochondrion distribution or SNB-GFP elimination phenotypes in RME neurons of ric-7(lf) animals, suggesting mitochondria may use distinct motor proteins in different neurons (Figure S3 G, H and I).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, mouse and zebrafish models of CMT2A have provided crucial information on the importance of Mfn2 in normal physiology and disease (Detmer et al, 2008;Vettori et al, 2011;Chapman et al, 2013;Bannerman et al, 2016). Moreover, recent studies in small model organisms such as the fruit fly Drosophila melanogaster and the nematode Caenorhabditis elegans have been instrumental in characterizing the role of mitochondria in neuronal health (Neumann & Hilliard, 2014;Rawson et al, 2014;Babic et al, 2015;Neumann et al, 2015;Melkov et al, 2016;Morsci et al, 2016;Yu et al, 2016). However, despite this progress, several outstanding questions and major goals for future research remain and are outlined below.…”
Section: Outstanding Questions and Future Directionsmentioning
confidence: 99%